Обработка данных контрастной компьютерной томографии в 2Б-режиме - Аврунин, О. Г.; Карпенко, Т. А. (ХНУРЭ, 2008)
Structural scheme 2D of system for visualization data of contrast computer tomography is review. Methods, algorithms and perspectives of development for post-processing and 2D, visualization data of contrast computer tomography are described: Increase brightness and contrast image, segmentation, median filtering, multiplanar reconstruction, outlines perspectives of their improvement
Keywords: томография; биомединженерия